THE EFFECT OF STRATEGIC HUMAN RESOURCE MANAGEMENT ON EMPLOYEE SATISFACTION: (CASE STUDY: SOMALI MEAT COMPANY IN MOGADIAHU SOMALIA ) - Gedow, Abukar; ABDULLE, MOHYADIN ISSE MOALLIM (IJRDO - Journal of Business Management, 2019)
The achievement of any company is directly connected to the satisfaction of the employees who represent that company, that retaining people is critical to the accomplishment of any organization. The main purpose of this study was to determine the effect of strategic human resource management on employee satisfaction in Somali Meat Company. The specific objectives of the study were to examine human resources management from employee promotions, employee commitment, and employee retention on employee satisfaction. The study population of 142 comprised all staff in Somali Meat Company. Non-probability sampling technique was used for managerial and non-managerial staff but 105 calculated as the sample size using Solvent’s formula. Data collection was done by a face-to-face personal filled in questionnaire method. The purpose of research is the numerical representation of the relevant data by coding and to analyze the data the researcher used Statistical Package for the Social Science (SPSS) version 20. Based on the findings in objective one presented that there is positive significance relationship between strategic human resource management and employee promotions which was indicated by Pearson correlation coefficient (r= 0.594 and p<= 0.05). The findings in objective two presented that there is positive significance relationship between strategic human resource management and employee commitment which was indicated by Pearson correlation coefficient (r= 0.745 and p <= 0.05). The findings in objective three presented that there is positive significance relationship between strategic human resource management and employee retention which was indicated by Pearson correlation coefficient (r= 0.462 and p <= 0.05) of Somali meat company in Mogadishu, Somalia. It is suggested that managers to be trained to use strategic human resources management and along with the increasing need for new skills and competencies of strategic human resources management as a result of changes in community, strategic human resources management training program is more important than ever. The research is based on the conceptualization so the better results can only be achieved through effect strategic human resource management and proper system in the organization.